Kinetics and Mechanism of Thermal Decomposition of Ni(II) Complex of 1-Amidino-3-phenylthiourea - GEORGE, ABRAHAM (Asian Journal of Chemistry, 2010)
Ni(II) complex of 1-amidino-3-phenylthiourea has been prepared, characterized and subjected to thermal analysis. The phenomenological, kinetic and mechanistic aspects of their decomposition have been studied. The Coats Redfern equation was used for the kinetic studies and various equations were invoked for the mechanistic studies and the Mampel equation gave the best fit.